Partial anomalous pulmonary venous return with dual drainage to the superior vena cava and left atrium with pulmonary hypertension - Nozomi Tanaka; Takayuki Jujo; Toshihiko Sugiura; Kaoru Matsuura; Takayuki Kobayashi; Akira Naito; Kengo Shimazu; Hajime Kasai; Rika Suda; Rintaro Nishimura; Jun Ikari; Seiichiro Sakao; et al. (Respiratory Medicine Case Reports, 2018)
Partial anomalous pulmonary venous return (PAPVR) is a rare congenital cardiovascular anomaly. A 68-year-old woman was referred to our hospital for detailed examination for pulmonary hypertension (PH). She had been diagnosed as having pulmonary artery dilation and suspected to have PH during a health check seven years prior. A contrast computed tomography showed that the right upper pulmonary vein (RUPV) returned to the superior vena cava (SVC) with a preserved normal connection to the left atrium (LA). Surgical repair was performed. We reported an extremely rare case of isolated PAPVR with PH showing dual drainage into the SVC and LA.